Immersed AC electrospray (iACE) for monodispersed aqueous droplet generation - Pan, Zehao (Biomicrofluidics, 2018)
We report a new immersed alternating current (AC) electrospray droplet generation method that can generate monodispersed water-in-oil droplets, with diameters ranging from 5 μm to 150 μm, in a stationary oil phase. This method offers high through-put, easy size tuning, and droplets with a viscous aqueous phase at high ionic strengths (raw physiological samples). Yet, it does not require coordinated flows of the dispersed/continuous phases or even a microfluidic chip. The design relies on a small constant back pressure (less than 0.1 atm) to drive the water phase through a nozzle (glass micropipette) and a non-isotropic AC electric Maxwell pressure to eject it into the oil phase. Undesirable field-induced discharge and nanojet formation at the tip are suppressed with a biocompatible polymer, polyethylene oxide. Its viscoelastic property favors the monodispersed dripping mechanism, with a distinct neck forming at the capillary tip before pinch-off, such that the tip dimension is the only controlling length scale. Consecutive droplets are connected by a whipping filament that disperses the drops away from the high-field nozzle to prevent electro-coalescence. A scaling theory is developed to correlate the droplet size with the applied pressure, the most important tuning parameter, and to determine the optimum frequency. The potential applications of this technology to biological systems are demonstrated with a digital loop-mediated isothermal amplification experiment, with little damage to the nucleic acids and other biomolecules, but with easy adaptive tuning for the optimum droplet number for accurate quantification.